Present and Future of the Russian Financial Market System - Oleg I Igorevich ZHEMERIKIN; Tatyana Yuryevna GAVRILENKO; Olga Victorovna GRIGORENKO; Svetlana Nicolaevna BUHANTSEVA; Elena Konstantinovna TKACHENKO (Communications of International Proceedings, 2021)
This article examines the current state of affairs in the Russian financial market: the behavior of the main market participants, the volatility of the national currency, the changes in consumer preferences, the capacity and behavior of the banking system in the current situation. The authors estimate the situation and express their opinion on the future of situation in Russian financial market system.
Keywords: Financial system; national currency volatility; credit institutions; consumer preferences.